Соединения L-лизина в фармакокоррекции нарушений энергетического метаболизма головного мозга при моделировании геморрагического инсульта - Беленичев, И. Ф.; Егоров, А. А.; Бєленічев, Ігор Федорович; Єгоров, Артем Анатолійович; Belenichev, I. F.; Egorov, A. A. (My University, 2013)
Стаття присвячена вивченню фармакологічних властивостей сполук L-лізину за умов моделювання геморагічного інсульту. За умов гострого порушення мозкового кровообігу за геморагічним типом на 4 добу експерименту спостерігається різке погіршення неврологічного статусу експериментальних тварин. На фоні введення сполук L-лізину в дозі 50 мг/кг відмічається зменшення неврологічного дефіциту, особливо в групах з введенням L-лізину есцинату, L-лізину сукцинату та «Лізинію». На 4 добу після відтворення геморагічного інсульту встановлено значне зменшення вмісту АТФ, АДФ, малату та пірувату на фоні підвищення вмісту лактату та АМФ в гомогенаті головного мозку, що свідчить про порушення енергетичного метаболізму. Експериментальна терапія сполуками L-лізину сприяла відновленню енергопродукції на 4 добу геморагічного інсульту. Найактивнішими енерготропними сполуками виявилися L-лізину сукцинат та «Лізиній», які підвищували вміст АТФ, АДФ, малату та пірувату, та знижували вміст АМФ та лактату. На нашу думку, висока енерготропна активність L-лізину сукцинату реалізується за рахунок активації шунта Робертса. Механізм дії «Лізинію» зумовлений наявністю в структурі цієї сполуки кислотного залишку тіотріазоліну, який має здатність активувати малат-аспартатний механізм продукції енергії. Ґрунтуючись на отриманих результатах, можна стверджувати про наявність у сполук L-лізину нейропротективної та енерготропної активності. This article describes the results of investigation of influence of L-lysine compounds (hydrochloride, succinate, aescinate and 3-methyl-1,2,4-triazolyl-5-thioacetate - «Lysinium») under hemorrhagic stroke modeling. Acute disturbance of cerebral circulation (type of hemorrhagic stroke) modeled by injection of autologous blood (20 mkg/ml) in the internal capsule of brain of albino male rats weighing 180-200 g. Compounds of L-lysine were injected intraperitoneally in dosage 50 mg/kg to the animals with hemorrhagic stroke daily from the 1st to 4th day. On the 4th day, injection of compounds of L-lysine to the experimental animals with intracerebral hemorrhage resulted in decreasing of neurological deficit on 1,66-10,5 units by the C. P. McGrow scale as compared the control group. The greatest activity was shown with L-lysine succinate and L-lysine 3-methyl-1,2,4-triazolyl-5-thioacetate («Lysinium»). L-lysine administration led to increasing of the content of ATP in brain tissue by 17-148 % and ADP by 15-62 %, and to decreasing of AMP content by 6-46 % as compared control group (p > 0,05) on the 4th day of the experiment. Injection of compounds of L-lysine to the experimental animals resulted also in the restoration of Krebs cycle functioning and in inhibition of anaerobic glycolysis in the brain (increasing levels of malate by 13-87 %, pyruvate by 18-136 % and decreasing of lactate level by 9-76%. The most active compounds of L-lysine were L-lysiniy succinate and Lysinium with explicit leadership of the latter. Lysinium was superior on all counts (p > 0,05) as compared to group treated with the Piracetam (dosage - 500 mg/kg) and control group. The mechanism of therapeutic action of L-lysine succinate realized through the compensatory succinateoxidase-related mechanism. However, in conditions of acute stroke the activity of succinateoxidase-related mechanism was complicated, which limited activity of this compound. Lysinium had a stronger energotropic action in comparison with other compounds of this serie, apparently, due to compensatory activation malate - aspartate shuttle mechanism.
Сполуки L-лізину в фармакокорекції порушень енергетичного метаболізму головного мозку при моделюванні геморагічного інсульту
Compounds of L-lysine in pharmacocorrection of disorders of energy metabolism of the brain in the modeling of hemorrhagic stroke
Keywords: острое нарушение мозгового кровообращения; L-лизин; нейропротекция; энергетический метаболизм; acute violation of cerebral circulation; L-lysine; neuroprotection; energy metabolism